The Influence of Functional Rehabilitation Braces with Resistance on Joint Coordination and ACL Force in Martial Artists Following ACL Reconstruction - Xiaoyan Wang; Haojie Li (Applied Sciences)
Objective: The resistive knee orthosis, as a novel rehabilitation device, is designed to provide resistance to joint movement during continuous walking, thereby enhancing the postoperative recovery effect. This study aims to explore the impact of such orthoses on the joint coordination patterns of martial artists after anterior cruciate ligament (ACL) reconstruction. Methods: A total of 44 martial artists who underwent ACL reconstruction were recruited and divided into an experimental group (EG, n = 22, using resistive braces) and a control group (CG, n = 22, using conventional braces). Assessments were conducted preoperatively (T0) and at 15 days (T1), 30 days (T2), and 60 days (T3) postoperatively. The changes in joint coordination patterns during the gait cycle were analyzed, and the ACL force was estimated using a musculoskeletal model. Results: At T2 and T3, compared with the CG, the EG exhibited a significantly larger peak knee flexion angle (p < 0.05). At T3, the EG showed higher hip–ankle in-phase coordination (p < 0.05), increased proximal hip–knee coordination (p < 0.05), and decreased knee–ankle anti-phase coordination (p < 0.05). In addition, the ACL force in the EG was significantly lower. Conclusions: The resistive knee orthosis can effectively improve the joint coordination of martial artists after ACL reconstruction and reduce the ACL force.